Find the solution to the following system using substitution or elimination y = -4x + 9 y = 3x - 5 A. (1.5) B. (1-2) C. (2.1) D. (14.373​

Respuesta :

Lanuel

Answer:

D. (14, 37)

Explanation:

Given the following data;

y = -4x + 9 ..........equation 1

y = 3x - 5 ............equation 2

We would solve the linear equation by using the substitution method;

Substituting equation 1 into equation 2, we have;

-4x + 9 = 3x - 5

-4x - 3x = -5 - 9

-x = - 14

x = 14

Now to find the value of y;

From equation 2

y = 3x - 5

Substituting the value of "x" into the equation, we have;

y = 3(14) - 5

y = 42 - 5

y = 37

ACCESS MORE